Challenges for rotational grazing practice: Views from non-adopters across the Great Plains, USA. (15th February 2020) - Wang, Tong; Jin, Hailong; Kreuter, Urs; Feng, Hongli; Hennessy, David A.; Teague, Richard; Che, Yuyuan
Abstract: Many ranchers who practice rotational grazing have experienced economic and ecological benefits. However, the adoption rate of rotational grazing has stagnated. To identify major challenges faced by non-adopters of rotational grazing as well as factors that affect the perceptions about different challenges, we conducted a mail survey of 4250 eligible ranchers in North Dakota, South Dakota and Texas, USA. Key categories of information obtained included basic ranch information, rotational grazing adoption status, and related information. Among 875 respondents, 40.4% identified themselves as non-adopters and perceived labor and water source constraints as the two major challenges, followed by high initial investment costs. This indicates the need for technical support and educational programs to address producers' concerns in addition to the monetary support from government subsidy programs. Findings from logistic regression analyses further indicate that landowners with higher quality soil, relatively more grassland (in both acres and percentage) and more owned land, generally perceive lower barriers to choosing rotational grazing practices and, therefore, may be a suitable target group for more effective outreach efforts and public fund investments to enhance the adoption of beneficial rotational grazing practices. Highlights: A landowner survey identified factors inhibiting the adoption of rotational grazing. Labor, water and high investment costs were key factors affecting adoption decision. Producers with higher ranch productivity perceived less adoption challenges. Producers with more owned grassland perceived less adoption challenges. Programs that address major concerns could enhance rotational grazing adoption.